Adaptation and growth response in some varities of rice under salinity stress - Wan Arfiani Barus; . Rosmayati (Syiah Kuala University, 2012)
Aim of this research was to get genotif that has the best growth and high adaptability in saline soil. Response of growth and adaptation were tested of 30 genotypes of rice. 30 genotypes respectively were observed and classified by the criteria : sensitive, moderate, tolerant and very tolerant by using a scoring method (salt injury score). Observation of growth and production showed that genotif IR 42 had the best growth and production as compared with other genotif.